THE ROLE OF PRANATA MANGSA IN SHAPING HABITUS AND ENHANCING SOCIAL RESILIENCE OF RURAL COMMUNITIES IN JAVA - Saifuddin Zuhri; Tuti Budirahayu (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
Pranata Mangsa is a traditional calendar system that has been passed down through generations by the Javanese people, particularly within the context of agrarian life. More than just a tool for determining planting seasons, this system also shapes behavioral patterns, values, and social norms that are deeply embedded in rural community life. From a sociological perspective, Pranata Mangsa contributes to the formation of habitus that is, ingrained dispositions and ways of thinking that are inherited and internalized through daily practices. Amid contemporary challenges such as climate change, globalization, and agricultural modernization, many rural communities continue to use the values of Pranata Mangsa as a foundation for their way of life. The habitus formed through this local wisdom is believed to enhance social resilience, which refers to the collective ability of communities to endure and adapt to social and ecological pressures. This study aims to explore the role of Pranata Mangsa in shaping the social habitus of rural communities and its contribution to strengthening their social resilience in the face of modern challenges. Referring to Pierre Bourdieu’s theory of habitus and the concept of social resilience, this research adopts a qualitative approach using case study methods in several villages in Central Java that continue to practice Pranata Mangsa. Data collection techniques include in-depth interviews, observation, and analysis of local documents. The results of this study are expected to provide deeper insights into the importance of preserving local wisdom as cultural capital in building socially resilient rural communities.